High Flow Nasal Oxygen as a Treatment Option for Acute Respiratory Distress Syndrome in Coronavirus (COVID-19) Infection - Jlal Bathish; Ayat Zabida; Muhammad Kashkush; Doron Mulla; Yael Berman; Lee Cohen; Aliza Zeidman (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
The ongoing outbreak of COVID-19 that began in Wuhan, China, has constituted a Public Health Emergency of International Concern, with cases confirmed in multiple countries. The outbreak of COVID- 19 in Israel, in March 2020 caused major changes in the routine work in hospitals mainly internal medicine wards . Hasharon hospital, a small community hospital in Petah Tikva was converted to corona patients admissions only. In accordance with this new reality internal medicine B department prepared itself to provide treatments tailored to the clinical needs of the Covid 19 patients and the quarantine conditions of these patients hospitalization. We report a confirmed case of COVID-19 who was diagnosed with ARDS and refused intubation. He was treated with High Flow Nasal Oxygen (HFNO) combined with medication and physiotherapy with very good results. This case highlights the importance of non-Invasive ventilation treatment.